Answer:
(x-10)(x+10)
Step-by-step explanation:
x^2 – 100
This is the difference of squares
x^2 - 10^2
We know that (a^2 - b^2) = (a-b) (a+b)
(x-10)(x+10)
Answer:
$95777.5
Step-by-step explanation:
change 7% to decimal = .07
91,000 * .07 = 5370 (annual interest)
5370 / 12 = 530.83 (monthly interest)
530.83 * 9 = 4777.5 (9 months interest)
91,000 + 4777.5 = 95777.5 (initial + 9 months interest)
Step-by-step explanation:
Length of title to board = (1/3) : (1/2) = 2 : 3.
Area of tile to board = (1/3)² : (1:2)² = 4 : 9.
For this case we have, by definition:
![a^{-b} =\frac{1}{a ^ b}](https://tex.z-dn.net/?f=a%5E%7B-b%7D%20%3D%5Cfrac%7B1%7D%7Ba%20%5E%20b%7D)
So, we have:
![\frac{1}{4}^{-\frac{1}{2}}=\frac{1}{(\frac{1}{4})^{\frac{1}{2}}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%3D%5Cfrac%7B1%7D%7B%28%5Cfrac%7B1%7D%7B4%7D%29%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%7D)
On the other hand we have that by definition:
![a^{\frac{1}{2}}=\sqrt{a}](https://tex.z-dn.net/?f=a%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%3D%5Csqrt%7Ba%7D)
Thus, the expression can be written as:
![\frac{1}{\sqrt {\frac{1}{4}}} =](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Csqrt%20%7B%5Cfrac%7B1%7D%7B4%7D%7D%7D%20%3D)
![\frac{1}{\frac{1}{\sqrt{4}}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Cfrac%7B1%7D%7B%5Csqrt%7B4%7D%7D%7D)
![\frac{1}{\frac{1}{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Cfrac%7B1%7D%7B2%7D%7D)
![\frac{1*2}{1*1}=2](https://tex.z-dn.net/?f=%5Cfrac%7B1%2A2%7D%7B1%2A1%7D%3D2)
So, we have:
![\frac{1}{4}^{-\frac{1}{2}}= 2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%3D%202)
Answer:
![\frac{1}{4}^{-\frac{1}{2}}= 2](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B4%7D%5E%7B-%5Cfrac%7B1%7D%7B2%7D%7D%3D%202)
Answer:
The second option shows the correct translation of 3 units to the right and 1 unit down.